The Expanding World of Human Leishmaniasis. Issue 5 (May 2017) - Cotton, James A.
Abstract : New Leishmania isolates form a novel group of human parasites related to Leishmania enrietti, with cases in Ghana, Thailand, and Martinique; other relatives infect Australian and South American wildlife. These parasites apparently cause both cutaneous and visceral disease, and may have evolved a novel transmission mechanism exploiting blood-feeding midges.